Species Composition of the Green Macroalgae (Chlorophyta) Species in the Waters of the Blue Marlin Beach, Gorontalo, Indonesia - La Nane (Fisheries and Society, 2023)
Blue Marlin Beach has been functioned as the marine tourism attraction by the local government of Gorontalo regent due to the beauty of the underwater. However the natural resources in the Blue Marli Beach have not been docuented, specifically for macroalgae. Therefore, this research aims to provide the data and information about species composition of the green macroalgae in the Blue Marlin Becah. This research was conducted for two months starting from November to December 2020. The measurement of GPS coordinate, seawater current, temperature, and wave actiion was concucted with Fishing Points Software. Observatory methode was performed in this study to collect the specimens. Then, all specimens was put-in the zipperbag and stored in the coolbox containing with the ice to protect the specimens in fresh. The results show that there are 6 species of the green macroalgae. Theya are Bornetella sphaerica, Caulerpa sertularioides, Valonia aegagropila, Boergesenia forbesii, Acetabularia caliculus, and Chaetomorpha crassa. The average of sea water temperatur during the study is 31Â°C with the seawater current is 0.1 m/s and wave is 0.2 m